1990
DOI: 10.1002/jez.1402550302
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic anhydrase in branchial tissues of osmoregulating shore crabs, Carcinus maenas

Abstract: Activities of carbonic anhydrase (CA) were determined in various organs of shore crabs, Carcinus maenas, acclimated to salinities of 10, 20, 30, 40, and 50%0. In addition, some properties of the branchial enzyme (effects of detergents, storage conditions, and specific inhibitors) were tested. Subcellular distribution of gill CA was analyzed by means of centrifugation procedures. In hemolymph no CA activity could be detected. In all other organs except gills activities were low and insensitive to salinity chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…No activity could be detected in the hemolymph which is consistent with other investigations (Brinkman, 1933;Ferguson et al, 1937;Sobotka & Kann, 1941;Henry & Cameron, 1982;B6ttcher et al, 1990a). Only a little CA activity was measured in heart, hypodermis and antennal gland; values did not exceed 3 U/rag protein.…”
Section: Distribution Of Ca Activity In Different Organs Of Eriocheirsupporting
confidence: 91%
See 1 more Smart Citation
“…No activity could be detected in the hemolymph which is consistent with other investigations (Brinkman, 1933;Ferguson et al, 1937;Sobotka & Kann, 1941;Henry & Cameron, 1982;B6ttcher et al, 1990a). Only a little CA activity was measured in heart, hypodermis and antennal gland; values did not exceed 3 U/rag protein.…”
Section: Distribution Of Ca Activity In Different Organs Of Eriocheirsupporting
confidence: 91%
“…minerahzation of calcified structures, acid base balance and, last but not least, ion transport (Henry, 1988b). With regard to crabs, it has been reported that CA activity, which is mainly locahzed in the posterior gills, is induced during acclimation of the animals to diluted media (Henry & Cameron, 1982;B6ttcher et al, 1990a) suggesting its possible role in ion regulation. Recently, the results of electrophysiological studies of posterior gills of tap water-adapted Chinese crabs suggested a participation of branchial CA in ion transport.…”
Section: Introductionmentioning
confidence: 99%
“…This belief is based on evidence obtained primarily from two experimental model species, the blue crab Callinectes sapidus and the green crab Carcinus maenas. In both species, CA is found with high activities in the primary organ of ion transport, the gill (Henry and Cameron, 1982a;Bottcher et al, 1990;Henry et al, 2002). The current view of branchial CA function is that the enzyme catalyzes the hydration of respiratory CO 2 as it diffuses through the gills from the hemolymph to the surrounding water, resulting in the production of H + and HCO 3 -in the intracellular fluid.…”
Section: Introductionmentioning
confidence: 99%
“…In light of extensive salinity-induced modification of CA activity in posterior gills of the hyper-regulating crab Callinectes sapidus, Henry and Cameron (1982 a) deduced that one of the potential roles of the enzyme is osmoregulation. In recent studies the CA of branchial tissues of crabs was shown to be localized in both the cytoplasm and the plasma membranes (Burnett and McMahon 1985, Henry 1987a, B6ttcher et al 1990a. In order to investigate the physiological roles of crab gill CA, techniques using intact individuals as well as isolated gill preparations were applied (Aldridge and Cameron 1979, Cameron 1979a, Burnett etal.…”
Section: Introductionmentioning
confidence: 99%